An Innovative Mobile Game for Detecting Cognitive Changes - Friesen, Marcia R.; Jeffrey, Ian; Leduc-Niven, Kyle; Mukhi, Shamir N.; McLeod, Robert D. (CMBES Proceedings, 2017)
This paper presents a mobile game for smartphones and tables, developed to detect the frequency and extent of memory slips. Memory slips are a natural phenomenon associated with cognitive changes as one ages. Although everyone will experience memory slips or more colloquially “senior moments”, not everyone who experiences memory slips will develop dementia. However, memory slips however can be symptomatic of more serious cognitive decline and the onset of dementias. In this work, we present an innovative means to quantitatively assess and monitor memory slips through a non-invasive mobile game.